JURIDICAL ANALYSIS OF THE FULFILLMENT OF RIGHTS AND ACCOMMODATIONS FOR PERSONS WITH DISABILITIES IN CORRECTIONAL INSTITUTIONS - Waskito, Sarwo; Saputra, Rio; Pakpahan, Novritsar Hasitongan; Khayru, Rafadi Khan; Wijaya, Kurnia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This literature study aims to critically analyze the fulfillment of rights, provision of reasonable accommodation, and the inclusiveness of rehabilitation programs for persons with disabilities in Indonesian correctional institutions. Employing a qualitative normative legal research method, this study examines international conventions, national legislation, and empirical reports. The findings reveal a significant normative-progressive yet implementative-deficient landscape. Indonesia has established a strong legal framework through the ratification of the Convention on the Rights of Persons with Disabilities (CRPD) and the enactment of Law Number 8 of 2016 concerning Persons with Disabilities, which mandate non-discrimination and reasonable accommodation. However, the factual conditions in prisons are starkly different. Physical facilities largely remain inaccessible, health and social services are not inclusively designed, and rehabilitation programs fail to accommodate specific needs, thereby perpetuating discrimination and hindering effective social reintegration. The study concludes that without translating legal mandates into detailed operational standards, adequate budgeting, and comprehensive training for correctional staff, the rights of incarcerated persons with disabilities will remain unrealized. It recommends the urgent development of a standardized service protocol, enhanced independent monitoring, and strategic partnerships to foster inclusive correctional practices.